Improving Indonesian Language Learning Outcomes Through Quizizz Learning Media In Elementary Schools - Agus Wahdian; Kusyairi Kusyairi; M. Khoiri M. Khoiri (Indonesian Journal Publisher, 2023)
The COVID-19 epidemic has significantly affected the education sector, resulting in a shift from traditional offline learning to online platforms. Quizizz is a media tool that teachers can utilize during online learning. The objective of this study is to ascertain whether the utilization of Quizizz as a learning medium has an impact on students' academic achievements. The research methodology employed is quantitative, utilizing a pre-experimental research design. The participants consisted of 26 fourth-grade kids. The data collection methods employed included the utilization of tests and questionnaires. The pre-test score yielded a mean result of 65.19, whereas the post-test score yielded a mean result of 88.08. Based on the research data analysis conducted using SPSS version 25, the results of the paired sample t-test indicate that the two-tailed significance value (sig) is 0.000, which is less than the significance level of 0.05. Therefore, we may conclude that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The study findings suggest that the utilization of Quizizz as a learning tool has a significant impact on students' academic performance in mathematics when accessed online at SDN Gunggung Sumenep.